Biomechanics of suspended-circles on pommel horse: What if knees are suspended? - Fujihara, T.; Gervais, P. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Training aids form a fundamental component of gymnastic training. Previous research has shown how a suspended aid changes biomechanics of circles on pommel horse. Building on these findings, the aim of the current study was to examine the influence of a modified use of the aid through the suspension of the gymnast at different positions. Discriminative biomechanical variables, which were identified in the previous research, were analysed to compare circles performed by a single gymnast between two conditions: with the aid around his knees and around his ankles. The results showed that changing the location of suspension had influences on both kinematics and kinetics of circles, implying the possibility of various use of a suspended aid.